Portable complex for controlled explosive reactive drilling of rocks - O. Solov’ev, Viktor; M. Shvedov, Igor’ (International Journal of Engineering and Technology, 2018)
The developed portable explosive-reactive complex for drilling-and-blasting operations in complex mining-geological conditions is considered. The basic design features of the complex are given. The main principles of ensuring the effectiveness of explosive-reactive drilling are formulated. The conditions for the appearance of the effect of the dynamic pressure on the rock of the complex ensuring its recoiling work are considered in detail.Â